2019
DOI: 10.1002/jclp.22845
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in public stigma, self‐stigma, and attitudes toward seeking help: A moderated mediation model

Abstract: Objective Stigma is commonly identified as a key reason that older adults are especially unlikely to seek mental health services, although few studies have tested this assumption. Our objectives were to: (a) examine age differences in public and self‐stigma of seeking help, and attitudes toward seeking help, and (b) see whether age moderates an internalized stigma of seeking help model. Methods A total of 5,712 Canadians ranging in age from 18 to 101 completed self‐report measures of public stigma of seeking h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
80
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(89 citation statements)
references
References 57 publications
6
80
3
Order By: Relevance
“…Furthermore, it supported the negative effect of anticipated stigma on help-seeking for mental health problems [ 11 ]. With regard to age, the reported association of older age with help-seeking [ 6 , 7 , 9 ] was not supported by our study, in which the contrary effect, an association with younger age, was found. Other direct effects on help-seeking reported from cross-sectional studies could not be replicated longitudinally, such as the help-seeking reducing effect of perceived and personal stigma [ 3 , 13 , 22 ], which also did not show on the level of bivariate correlations, or the help-seeking increasing effect of earlier help-seeking intentions [ 13 , 23 , 24 ], and of female sex [ 6 , 8 ].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Furthermore, it supported the negative effect of anticipated stigma on help-seeking for mental health problems [ 11 ]. With regard to age, the reported association of older age with help-seeking [ 6 , 7 , 9 ] was not supported by our study, in which the contrary effect, an association with younger age, was found. Other direct effects on help-seeking reported from cross-sectional studies could not be replicated longitudinally, such as the help-seeking reducing effect of perceived and personal stigma [ 3 , 13 , 22 ], which also did not show on the level of bivariate correlations, or the help-seeking increasing effect of earlier help-seeking intentions [ 13 , 23 , 24 ], and of female sex [ 6 , 8 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Based on the results of the PCA and previous studies, we formed one latent variable for 'perceived stigma'. The variables 'WSD' [19], 'help-seeking intention' [13,23,24], 'anticipated stigma [11], 'age' [7], 'sex' [30], 'functional deficit' [9], 'help-seeking at baseline' [9,10,13] were modelled as observed variables. The pathways from stigma via own help-seeking assumptions (i.e., help-seeking intentions) to help-seeking behaviour including all likely associations between latent and manifest variables were modelled in a SEM.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Stigma was also highlighted as a common barrier, primarily in older individuals. This is contradictory with previous findings from studies in Canada which suggest that stigma decreases and positive attitudes to helpseeking increase with age (Mackenzie, Gekoski, & Knox, 2006;Mackenzie et al, 2019), indicating potential differences across countries regarding social norms and the way in which stigma is experienced (Wester, 2008). These differences have not been accounted for in the literature and require further investigation.…”
Section: Discussioncontrasting
confidence: 99%